Minimum Wage Determination For Employees/Workers : A Principle of Legal Protection on Manpower - Nobella Indradjaja; Suwarno Abadi (Journal of Law, Politic and Humanities, 2025)
Indonesian workers are vulnerable to becoming victims of white collar crime, as the basic things they are entitled to are often not paid by the company. To minimize the losses experienced by Indonesian workers, the government has established several legal steps which are the core to this research. Using a normative juridical approach, this research focuses to find out the legal grounds and steps that workers can take to fight for justice. The results of the research show that: One, there are regulations in Article 27 paragraph (2) of the 1945 Constitution and Article 88 paragraph (1) of Law No. 6 of 2023 concerning the Stipulation of Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation into Law which protects workers from wage violations (one of which is minimum wage). Two, there are legal routes that workers can take if industrial relations conflicts continue: Bipartite, Mediation, and Industrial Relations Court.